A double blind study to evaluate the efficacy of Distribution of F-Latency (DFL) in the detection of cervical radiculopathy and myelopathy (Bangladesh Journal of Medical Physics, 2015)
Distribution of F-Latency (DFL) is a new parameter in peripheral nerve conduction measurement and an important application of this new technique is the detection of Cervical Radiculopathy and Myelopathy (CRM) at an early stage through an evaluation of its pattern. Typically a single sharp peak corresponds to normalcy while double peak or a broad peak represents pathology. The current study is an exercise in validating DFL as a screening tool for CRM by comparing the data obtained from an extended pool of subjects (56 median nerves of 28 persons) against corresponding MRI findings through a double blind study. Subject selection was done randomly A 1.5 Tesla MRI scanner and a home built Computerised EMG equipment were used for this study. Analysis of data gave a correct prediction or efficacy of 75%, sensitivity of 77% and specificity of 50%. The present study establishes DFL on a stronger footing for assessment of cervical radiculopathy and myelopathy, whether due to spinal cord or nerve root compression. In combination with conventional simple clinical tests, DFL is expected to give better information for diagnosis of CRM. Being a non-invasive technique requiring virtually zero expenditure in consumables, it promises greater access to patients, and could be used for extensive prevalence study, which cannot be performed using MRI. The capability of DFL in detecting subclinical stages of CRM holds a promise as an awareness development tool alongside screening for neuropathy.Bangladesh Journal of Medical Physics Vol.7 No.1 2014 46-55